(untitled) - Hickman, Craig R. (New York, 2002)
The book teaches new techniques, new ways of thinking and evolving, and ways of overcoming the fear of change that destroys even the strongest companies. An Innovator's Tale will show you how to embrace and conquer change and turn a company into a paragon of innovative thinking. It goes beyond " thinking outside the box" and embraces new ways of imagining products and concepts. It offers the tools to reinvent a company through creativity, making it healthy and strong for the twenty-first century.
Keywords: Business intelligence,Executive ability,Trí tuệ kinh doanh,Năng lực quản trị; Mẫu chuyện